Enhancing Students’ Artistic Skills through Integration of National Traditions in Visual Arts Lessons - Nasulloyeva Sarvinoz Komiljon qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article explores strategies for enhancing students’ artistic skills by integrating national traditions into visual arts education. It focuses on developing creativity, aesthetic literacy, and an understanding of cultural heritage. The study discusses practical, project-based, and interactive teaching methods that allow students to apply traditional artistic elements in contemporary visual art projects. The article also provides guidance for educators on combining cultural heritage with modern pedagogical strategies to maximize engagement and learning outcomes.